Peran Kepala Desa Dalam Meningkatkan Kinerja Perangkat Desa Di Desa Lairuru Kecamatan Umalulu Kabupaten Sumba Timur - Amah, Oktavina Ana; Tuan, Yohanes; Asnawi, Norani (Artemis Law Journal, 2025)
The village head has full responsibility for the success of the implementation of village government that has targets that must be achieved, the village apparatus can be said to be good if the performance is in accordance with the targets that must be achieved. Where there are still complaints from the community until now that the Lairuru village government has not provided services in accordance with the needs of the community optimally. For example, village officials are often not at the village office when the community will take care of administrative needs, for example taking care of the certificate of incapacity, taking care of family cards, taking care of domicile certificates, managing the making of birth certificates, and identity cards. This is because the village head in leading the implementation of the village government is not firm in relation to the performance of the village apparatus. In carrying out their duties, the village head is responsible for leading and coordinating their respective subordinates and providing guidance and instructions for the implementation of subordinate duties.